From Racial Resistance to Racial Consciousness: Engaging White STEM Faculty in Pedagogical Transformation. (June 2019) - Haynes, Chayla; Patton, Lori D.
Professor Arnie Copper is among the many science, technology, engineering, and mathematics (STEM) faculty who view the learning of STEM curriculum as an intellectual exercise that is race-neutral. In this case, the authors use the White Racial Consciousness and Faculty Behavior model to illustrate how racially minoritized students can experience the classrooms of White STEM faculty who fail to see connections between their teaching, course content, and racial justice. Institutional leaders and faculty developers can use this case to generate a timely critique of the enduring racism shaping higher education and fostering hostile learning conditions on college campuses.